Vaga-lumes de tocha: o ser, o fazer e os dizeres da Quinta Turma da Escola Família Agrícola da Região de Alagoinhas - Araujo, José Conceição Silva (2018)
The "torch firefly" is a variety of fireflies, so-called popularly, because the light does not appear on its body, but the brightness of it on the ground in a circular way. The higher they fly, the greater the luminous circle (torch) that it reflects on the ground.This work aims to analyze how the experience with the Alternance Pedagogy, as guiding the praxis of Agricultural Family School of Alagoinhas’ Region (EFARA) has influenced the lives of its former studants. EFARA started in 1983 in the region of Alagoinhas, with the purpose of attending children of rural workers and forming local community leaders.For that purpose, we have chosen the 1990 graduated class (that studied in the school from 1988 to 1990), which we call the "Fifth Class". Like torch fireflies, graduates of the Fifth Group, helped illuminate the way of this research. The research, when studying the school, identifies that the institution went through four phases in its 35 year-history. Currently, the school offers the Technical Course in Agriculture and Livestock in High School for 87 students. The methodology of qualitative research developed from a critical perspective and had as categories of analysis the Agricultural Family Schools, Alternance Pedagogy (AP) and EFARA graduates.The study focused on the trajectory of 12 graduates of the "Fifth Class" and it used as instruments of data collection, the application of questionnaires, semi-structured interviews, "letters" of the subjects and institutional documents found in the school and personal collections.The results of the research revealed that these graduates throughout their adult lives distanced themselves from the initial proposal of the school, with practice of Alternance Pedagogy, in several important aspects: the perspective of "permanence in the countryside" was not fulfilled for at least half of the graduates, and most of graduates do not work in the countryside; they were unable to continue their studies; distanced themselves from the processes of social and political organization; distanced themselves from the institution and its community patrimony. The data also revealed that, in spite of this, the graduates consider the experience in school with the Alternance Pedagogy, and without doubt, they would recommend such experience for the current youth as a way of overcoming difficulties and the possibility of achieving a satisfactory educational formation. Such research and its announced contradictions can have an important contribution for debates of the Alternance Pedagogy and its theoretical methodological challenges in the political project of education of the countryside.